Diversification of the food industry of Kazakhstan in the conditions of globalization (International relations and international law Journal, 2018)
Today, in the economy of Kazakhstan, industry plays a huge role. The share of industrial production is about 30% of the gross domestic product. At industrial enterprises of Kazakhstan, work nearly 20% of the population employed in the economy. Industrial enterprises are fully provided with their raw materi- als, which contributes to their development. The food industry plays one of the most important roles in the economy of the Republic of Kazakhstan. According to the Statistics Committee of Kazakhstan for 2017, the share of this sector in the total industrial output of the Republic is 7.0%, whilst manufacturing industry is 19.8%. The food industry of Kazakhstan is among the most dynamic segments of the country’s economy. The predominant share in the structure of the relevant industry owned by grain processing, production of milk, bread, meat, fruit and vegetable cultivation, activities of oil and fat companies. Sig- nificant needs of the RK for food imports are still being preserved. This can predetermine the prospects for further growth of the relevant segment as an instrument for import substitution.The government of the country also plays a significant role in the development of the food industry      in Kazakhstan. So, the authorities of Kazakhstan call large-scale programs to support manufacturers.Mainly, this is subsidizing, reducing interest rates on corporate loans, facilitating the acquisition of fixed assets. It is expected that during the implementation of the relevant initiatives by government agencies to support businesses several trillion tenge will be invested. It is also planned to adjust a number of provisions of the tax legislation in order to optimize the interaction between the enterprises of the food industry and the state in the context of budgetary allocations.This article analyzes the food industry in Kazakhstan, examines the main problems of this industry and suggests ways to improve the efficiency of the food industry in the context of globalization.Key words: food industry, enterprises, globalization, export, import, food.